2021
DOI: 10.1101/2021.01.19.427293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A conserved regulatory module regulates receptor kinase signaling in immunity and development

Abstract: Ligand recognition by cell-surface receptors underlies development and immunity in both animals and plants. Modulating receptor signaling is critical for appropriate cellular responses but the mechanisms ensuring this are poorly understood. Here, we show that signaling by plant receptors for pathogen-associated molecular patterns (PAMPs) in immunity and CLAVATA3/EMBRYO SURROUNDING REGION-RELATED peptides (CLEp) in development employ a similar regulatory module. In the absence of ligand, signaling is dampened t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Consistent with the importance of phosphorylation in activating RK-mediated immune signaling, phosphatases have been identified that directly interact with several such RKs. The PP2C isoforms XB15 and POLTERGEIST-LIKE 4 and 5 (PLL4 and 5) are homologs from rice and Arabidopsis that were identified as interactors of XA21 and Arabidopsis EFR, respectively, where they act as negative regulators of immunity (DeFalco et al, 2021;Holton et al, 2015;Park et al, 2008). Other PP2Cs have been identified that regulate CERK1 (Liu et al, 2018), while a PP2A complex was found to negatively regulate the activation of BAK1 (Segonzac et al, 2014).…”
Section: Rk Phosphorylation Within Prr Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with the importance of phosphorylation in activating RK-mediated immune signaling, phosphatases have been identified that directly interact with several such RKs. The PP2C isoforms XB15 and POLTERGEIST-LIKE 4 and 5 (PLL4 and 5) are homologs from rice and Arabidopsis that were identified as interactors of XA21 and Arabidopsis EFR, respectively, where they act as negative regulators of immunity (DeFalco et al, 2021;Holton et al, 2015;Park et al, 2008). Other PP2Cs have been identified that regulate CERK1 (Liu et al, 2018), while a PP2A complex was found to negatively regulate the activation of BAK1 (Segonzac et al, 2014).…”
Section: Rk Phosphorylation Within Prr Complexesmentioning
confidence: 99%
“…RLCK-VII/PBLs, however, are highly active kinases and have been found to directly phosphorylate numerous substrate proteins to initiate PTI signaling (discussed below). Among RLCK-VII isoforms, BOTRYTIS-INDUCED KINASE 1 (BIK1) (Veronese et al, 2006) and its close homolog PBL1 have emerged as key convergent signaling hubs downstream of diverse PRR complexes (DeFalco et al, 2021;Kadota et al, 2014;Li et al, 2014;Liu et al, 2013;Lu et al, 2010;Monaghan et al, 2015;Ranf et al, 2014;Zhang et al, 2010). Activation of BIK1 relies on its phosphorylation, which can be rapidly detected upon PAMP perception (Lu et al, 2010;Zhang et al, 2010).…”
Section: Activation Of Rlcks By Prrsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CLV3 peptide is perceived by a leucine-rich-repeat (LRR) receptor kinase, CLAVATA1 (CLV1), which interacts with coreceptors of the CLAVATA3 INSENSITIVE RECEPTOR KINASES (CIK) 1-4 family (Clark et al, 1997;Cui et al, 2018). CLV1 activation involves autophoshorylation, interaction with membrane-associated and cytosolic kinases and phosphatases (Blümke et al, 2021;Defalco et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The CLV3 peptide is perceived by a leucin-rich-repeat (LRR) receptor kinase, CLAVATA1 (CLV1), which interacts with coreceptors of the CLAVATA3 INSENSITIVE RECEPTOR KINASES (CIK) 1-4 family (Clark et al, 1997; Cui et al, 2018). CLV1 activation involves autophoshorylation, interaction with membrane-associated and cytosolic kinases and phosphatases (Blümke et al, 2021; Defalco et al, 2021). Furthermore, heterotrimeric G-proteins and MAPKs have been implicated in this signal transduction cascade in maize and Arabidopsis (Betsuyaku et al, 2011; Bommert et al, 2013; Ishida et al, 2014; Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%